(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
Antibacterial susceptibility patterns of some bacteria isolated from selected barbing salons in parts of Northern Nigeria was studied for the purpose of developing a disinfectant system suitable for use in salons. The K-values for selected cells ranged from 0.0072 to 0.0399 (benzalkonium chloride), and from 0.0062 to 0.1338 (propylene glycol) as against a range of 0.0147 to 0.1343 when the two chemicals were combined. The observed D-value range of 64.5 to 99 (benzalkonium chloride), 31.5 to 105 (Propylene glycol) and 21 to 24 (admixture of the two chemicals) were exploited in the development of "SALONSAFE" - a salon disinfectant that was able to eliminate 10/ ml (of the most resistant bacterial isolated in these studies) completely in 60 seconds.